PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR - Akmal, Rahayu Mayeni; Ratna, Ellya; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of the research is describe the influence of cooperative model of TPS type by using image media the skill of procedure text writing for student at VIII grade in 2 Junior High School Padang Panjang. The research method is experimental. The results of this research are three: (1) the skill of the procedure text before using the cooperative model of TPS type by using image media are in the qualifications Enough (64,88), (2) the skill of the procedure text after using the cooperative model of TPS type by using image media are in the qualifications Good (81,55), (3) the skill of the procedure text after using cooperative model of TPS type by using image media batter than before using the model of cooperative of TPS type by image mediaÂ Kata kunci: pengaruh, kooperatif, TPS, gambar, teks prosedur